2001
DOI: 10.1136/ard.60.10.968
|View full text |Cite
|
Sign up to set email alerts
|

Shape of the intercondylar notch of the human femur: a comparison of osteoarthritic and non-osteoarthritic bones from a skeletal sample

Abstract: Objectives-To compare objectively the shape of the intercondylar notch in human osteoarthritic and non-osteoarthritic femora. Methods-A sample of 96 human femora from a large skeletal population were selected for study. These femora included subjects with evidence of late stage osteoarthritis (that is, with eburnation present) and subjects with no such evidence. The distal end of the femur, viewed axially, was recorded with a video camera, and digitised computer images were produced. The outline of the interco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
55
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 21 publications
4
55
1
2
Order By: Relevance
“…Because our further preliminary work revealed that knees from some 42-week-old guinea pigs lacked the ACL entirely, it is likely that notch width narrowing causes impingement and damage of the ACL, as seen in humans. Our findings are therefore consistent with the hypotheses of Wada et al (10) and of Shepstone et al (23), that osteophyte formation is an event secondary to the onset of OA and a result of ACL laxity. This study is the first to show the time course of events involving ACL function and notch impingement in a way that has not been possible in humans.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Because our further preliminary work revealed that knees from some 42-week-old guinea pigs lacked the ACL entirely, it is likely that notch width narrowing causes impingement and damage of the ACL, as seen in humans. Our findings are therefore consistent with the hypotheses of Wada et al (10) and of Shepstone et al (23), that osteophyte formation is an event secondary to the onset of OA and a result of ACL laxity. This study is the first to show the time course of events involving ACL function and notch impingement in a way that has not been possible in humans.…”
Section: Discussionsupporting
confidence: 82%
“…Narrowing of the intercondylar notch has also been associated with OA severity (10,23) and deterioration of the ACL (10,22). Wada et al (10) and Shepstone et al (23) reported a significantly reduced NWI in the setting of moderate-to-severe OA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In figure 5, higher mean and standard deviation of the deformation values are realized on the patellofemoral compartment of the trochlear (femoral) side. Previous distal femoral bone studies have indicated that shape changes in the intercondylar notch when comparing normal against diseased subjects as a discriminant of OA (Shepstone et al, 2001) and hence has there is a possibility of a potential link between the findings of this study to what has been observed in the past.…”
Section: Discussionmentioning
confidence: 43%
“…Wada et al [13] concluded that the intercondylar notch of the knee is significantly smaller in knees with severe OA relative to normal knees. Shepstone et al [14] studied human skeletons and created video images of an axial view of the distal femur and found that a flattened shape to the intercondylar notch of the femur was associated with the presence of late-stage OA. Therefore, it is reasonable to assess the relationship between the morphology of the intercondylar notch and OA.…”
Section: Discussionmentioning
confidence: 99%